Esports and sport: Approaches between virtual motion body culture and cyber megaevents - Dias dos Santos Leal, L.; Perrucci Toledo Machado, R. (Olimpianos - Journal of Olympic Studies, 2019)
Electronic Games are gaining more and more power of cultural and economic impact on our society, until they reach a point where at the beginning of this century they begin to attract the attention of researchers from various areas, including physical education. in its different aspects of seeing the same phenomenon. This paper starts from this point, trying to make an analysis of this current situation s from the cultural production (literature, internet, television), using hermeneutics as methodology, that is, to seek meaning in what games mean. The possibility of playing online, and the emergence of the concept of e-sports brings a new possibility within cyberculture. People in different places, with different characteristics, different histories, can interact within cyberspace without carrying any of the characteristics of "real life", and at the same time, as a consequence of this cultural diversity, can build something new from the mediated established interaction. by the virtual environment. As this situation requires movement, not necessarily physical movement, we adopt the term "Virtual Movement Body Culture" to bring this manifestation to the area of Physical Education. It is clear that we are dealing with a cultural production of the human movement, and it is also clear that it is the people who are producing this knowledge from playful demands through the possibilities allowed by cyberspace. The culmination of this process is the emergence of cyber mega events. Understanding and appropriating this framework is fundamental for us to understand this new social manifestation within its own peculiarities. They have their own characteristics that set them apart from the cultural manifestations we have known so far, and this is where we need to begin our understanding.